Pemanfaatan Sosial Media untuk Meningkatkan Penjualan Produk UMKM di Desa Aek Loba Afdeling 1 - Fikri Rizalsyah Harahap; Uswah Hasanah (Fakultas Teknik Universitas Cenderawasih, 2024)
Nowadays, everyone can access the internet easily. In the digital era, micro, small and medium enterprises MSMEs must immediately change the way they sell their products via social media. The aim of this activity, which is oriented towards community service, is to help MSMEs in Aek Loba Afdeling 1 Village, Aek Kuasan District, Asahan Regency, face the economic crisis and it is hoped that they can increase sales by helping with their marketing management in the digital era. The method used in this community service is carried out face to face (on the spot training). Data collection used was observation, interviews and documentation. The result of this community service is to teach people how to use social media to market so they can increase sales.